2018
DOI: 10.1002/anie.201802083
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in the Structure, Chemical State and Catalytic Selectivity of Cu Nanocubes during CO2 Electroreduction: Size and Support Effects

Abstract: In situ and operando spectroscopic and microscopic methods were used to gain insight into the correlation between the structure, chemical state, and reactivity of size- and shape-controlled ligand-free Cu nanocubes during CO electroreduction (CO RR). Dynamic changes in the morphology and composition of Cu cubes supported on carbon were monitored under potential control through electrochemical atomic force microscopy, X-ray absorption fine-structure spectroscopy and X-ray photoelectron spectroscopy. Under react… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

22
363
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 351 publications
(386 citation statements)
references
References 47 publications
22
363
1
Order By: Relevance
“…The resulting electrocatalysts show higher current densities and selectivities for ethylene (20 % < FEnormalC2normalH4 < 45 %) and oxygenated products compared to a planar electrode, although hydrogen is still the predominant product (40 % < FEnormalH2 <60 %). Unfortunately, these systems suffer from fast structural reconstruction/degradation and performance decay during catalysis, possibly due to the applied electrochemical bias . As a consequence, the sustained influence of Cu morphology on the resulting products still remains elusive.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…The resulting electrocatalysts show higher current densities and selectivities for ethylene (20 % < FEnormalC2normalH4 < 45 %) and oxygenated products compared to a planar electrode, although hydrogen is still the predominant product (40 % < FEnormalH2 <60 %). Unfortunately, these systems suffer from fast structural reconstruction/degradation and performance decay during catalysis, possibly due to the applied electrochemical bias . As a consequence, the sustained influence of Cu morphology on the resulting products still remains elusive.…”
Section: Introductionsupporting
confidence: 92%
“…These structural observations contrast with previous reports on nanostructured copper electrodes . This is the first example of stable copper nanocubes under electrocatalytic conditions over prolonged reaction times (>40 h, Figure S16).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, and in clear conflict with those works, a greater number of recent studies implementing in situ or post‐mortem X‐ray absorption, photoelectron or electron energy loss spectroscopies (XAS, XPS, EELS) have concluded that the initial oxide does not get completely reduced in the course of the CO 2 ‐reduction process. Moreover, those same works additionally assigned the enhanced selectivity for ethylene/alcohols production displayed by these catalysts to the presence of remnant oxide within their (sub‐)surface …”
Section: Introductionmentioning
confidence: 96%
“…The validation of these conflicting lines of thought is complicated by the high surface roughness intrinsic to these Cu 2 O catalysts, since their eventual reduction to Cu 0 would translate into an abundance of [100](‐stepped) analogous domains and/or in a high surface pH that would justify the CO 2 ‐to‐ethylene selectivity displayed by these materials. Additionally, their correspondingly large content of surface grain boundaries prone to re‐oxidation upon contact with trace amounts of oxygen (e. g., during sample transfer for post‐mortem characterization) could cause the apparent presence of remaining (sub‐)surface oxides asserted in the above studies . Thus, to suppress the ambiguous effects of the surface roughness on the oxide's selectivity and post‐mortem oxidation state, in this work we prepared quasi‐planar, low‐roughness Cu 2 O thin films (TFs) and used them as CO 2 ‐reduction electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Previous experimental and theoretical studies demonstrated that Cu(100) is the most favorable crystal orientation for the C−C coupling process . However, the surface of Cu electrodes under electrochemical environments often undergoes reconstructions induced by applied potentials, the intermediates formed during CO 2 RR, as well as specifically adsorbed anions . On the other hand, some anions either present in the electrolyte or adsorbed on the electrode surface, have been shown to play a vital role in the dynamic evolution of the catalyst structure under reaction conditions as well as the activity and selectivity of CO 2 RR.…”
Section: Introductionmentioning
confidence: 99%